2003
DOI: 10.1002/jlcr.791
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of tritium labelled 3(R)‐HETE and 3(R),18(R/S)‐DiHETE through a common synthetic route

Abstract: SummaryAn efficient procedure for the synthesis of 3-hydroxyoxylipins labelled with tritium on all double bond positions is reported. The synthetic scheme involves a joint route for the formation of tetraacetylenic precursors followed by stereoselective reduction of the triple bonds either with hydrogen or tritium. The final tritiated products were obtained with specific activities ranging from 1.65 to 1.80 Ci/mmol. Copyright # 2003 John Wiley & Sons, Ltd.Key Words: tritium labelled fatty acids; 3(R)-hydroxy-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…These studies showed that these oxylipins are mainly associated with yeast sexual stages (asci), where they, among others, coat the outer surfaces of ascospores ( Fig. 2) (Bhatt et al, 1998;Kock et al, 1998;Groza et al, 2002Groza et al, , 2004. So far, in addition to antibody mapping, chemical analysis by GC-MS in most cases has confirmed the presence of 3-OH oxylipins.…”
Section: Distribution Of 3-oh Oxylipins In Yeastsmentioning
confidence: 93%
“…These studies showed that these oxylipins are mainly associated with yeast sexual stages (asci), where they, among others, coat the outer surfaces of ascospores ( Fig. 2) (Bhatt et al, 1998;Kock et al, 1998;Groza et al, 2002Groza et al, , 2004. So far, in addition to antibody mapping, chemical analysis by GC-MS in most cases has confirmed the presence of 3-OH oxylipins.…”
Section: Distribution Of 3-oh Oxylipins In Yeastsmentioning
confidence: 93%
“…Actually, the presence of a significant amount of under-reduced structures is all the more surprising, since the authors did not report the use of any reagent to poison the palladium surface. The reaction conditions are compatible with the presence of many functional groups, including methyl ester, 315,316,320,354,355 conjugated ester, 356,357 OBO ester, 340,358 carboxylic acid function, 324,359,360 free hydroxyl groups, 314,315,317,319,322, 324,326,329,341 epoxide, 319,327,328,335,349 acetate, 361 acetal, 356 M O M , 3 1 4 m o n o m e t h o x y t r i t y l , 3 0 7 N -t o s y l , 3 4 0 THP, 318,325,343,362−364 benzoyl, 351,365,366 and allylic benzoyl 321 groups, but also sulfides, 367 OTES, 323 OTBDMS, 320,335,368 OTBPS, 307,332,340,343,355,361 PMB, 356,369 quinone moiety, 324 chlorine atom, 345 and 1,3-dioxolane, 342 1,2-dioxolane, 370 or 1,2-dithiolanes, 360 thiazolidin-2-one 1, 356 and cyclopropane.…”
Section: The Lindlar Catalystmentioning
confidence: 99%
“…The amount of palladium catalyst varies notably from one report to another. Most authors add about 5–10 wt % catalyst, but the quantity is sometimes increased up to a 2/1: “catalyst” to substrate ratio. , The experiment is sometimes stopped to be launched again with another batch of catalyst.…”
Section: Applications In Total Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by displacing a halogen atom using tritium gas, as in the preparation of 51 2,3,4,9-tetrahydro-1H-carbazoles 52 or neurokinini-1 receptor ligands. 53 Another technique which gives very high specific activity products is tritiation by the catalytic reduction of acetylenic bonds, a method used in the synthesis of labelled 3-hydroxyoxylipins 54 and a pyrrolopyrimidine A (2B) antagonist. 55 Catalytic tritium reduction of 2-(5H)-furanone was used to make 56 labelled c-hydroxybutyric acid.…”
Section: Tritium [ 3 H]mentioning
confidence: 99%